2004
DOI: 10.1111/j.0742-2822.2004.03083.x
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Stress Echocardiography in the Study of Patients with Dilated or Hypertrophic Cardiomyopathy

Abstract: Stress echocardiography is a useful noninvasive modality for measuring dynamic outflow gradient and contractility changes in patients with hypertrophic cardiomyopathy (HCM) or dilated cardiomyopathy (DCM). In patients with HCM, stress echocardiography may determine the degree of outflow tract obstruction at rest and with activity, can detect occult systolic dysfunction in symptomatic patients with a normal resting left ventricular ejection fraction, and can also be utilized to monitor the efficacy of treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
18
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 55 publications
2
18
0
Order By: Relevance
“…31 Three studies reported effects of AT1-R antagonists in patients with non obstructive HCM. 32 4,35 in the present study, increase in exercise tolerance correlated with improvement in myocardial systolic and diastolic function. Regression of LV mass appeared to be one of the major mechanisms underlying this improvement.…”
Section: Angiotensin II Blockade In Hcmsupporting
confidence: 68%
See 2 more Smart Citations
“…31 Three studies reported effects of AT1-R antagonists in patients with non obstructive HCM. 32 4,35 in the present study, increase in exercise tolerance correlated with improvement in myocardial systolic and diastolic function. Regression of LV mass appeared to be one of the major mechanisms underlying this improvement.…”
Section: Angiotensin II Blockade In Hcmsupporting
confidence: 68%
“…HCM had been diagnosed on the basis of echocardiography showing a nondilated, hypertrophied LV (any wall thickness Ͼ15 mm) in the absence of known causes of LV hypertrophy, hypertension, or valvular disease. 18,19 Exclusion criteria were as follows 1 : hypertrophic obstructive cardiomyopathy defined as presence of a resting gradient in LV outflow tract Ն30 mmHg or in right ventricular outflow tract Ն15 mm Hg at Doppler echocardiography 2 ; atrial fibrillation 3 ; treatment with ACE inhibitors or AT1-R antagonists at any time in the past 4 ; contraindications to AT1-R antagonists 5 ; coronary artery disease, renal failure, hepatic disorders or serious intercurrent illness limiting survival; and 6 poor echocardiographic image quality. The study protocol was approved by the Medical Ethics Committees of all participating institutions and informed consent was obtained from all patients.…”
Section: Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…While one useful modality for detecting L-LVOTO is dobutamine stress echocardiography (DSE), 6) it cannot be performed easily in all hospital settings. Accordingly, there is a need for identification of the basic echocardiographic features that suggest the presence of L-LVOTO in non-LVH patients.…”
Section: Eft Ventricular Outflow Obstruction (Lvoto) Occurs Inmentioning
confidence: 99%
“…4,5) Although L-LVOTO in non-LVH patients has a potential to induce cardiovascular events, the prevalence, clinical course, and prognosis of L-LVOTO in non-LVH patients still remain elusive. Therefore, such patients have to be followed carefully and their clinical outcome characterized.While one useful modality for detecting L-LVOTO is dobutamine stress echocardiography (DSE), 6) it cannot be performed easily in all hospital settings. Accordingly, there is a need for identification of the basic echocardiographic features that suggest the presence of L-LVOTO in non-LVH patients.…”
mentioning
confidence: 99%